Analysis of degraded land suitability and regional comparative advantages for maize development in the Gorontalo sustainable agriculture areas, Indonesia - Rayes, Mochtar Lutfi; Nurdin, N; Listyarini, Endang; Agustina, Christanti; Rauf, Asda (Brawijaya University, 2023)
Maize has attracted the attention of local governments due to its high yield potential and economic prospects, but the strategic value of this commodity has not been specific to particular locations. Therefore, this study aimed to assess degraded land suitability and determine the regional comparative advantages for maize development in the Gorontalo sustainable agriculture areas. The suitability class was assessed using Automatic Land Evaluation System software, while comparative advantages were determined using input-output and regional analysis. The input-output analysis was based on maize farming data from interviews with 80 farmers. This study also employed location quotient, specialization index, and localization index analyses based on maize, rice, and soybean production data for 2014, 2016, and 2018. The results showed that land degradation caused by soil erosion was dominated by moderate, heavy, and very heavy categories. Most of the actual land suitability for maize was classified as marginal suitable (S3) but became very suitable (S1) and moderately suitable (S2) after the limiting factors were improved. Furthermore, maize was profitable for the land suitability classes of S1, S2, and S3, and the commodity was most concentrated in Mootilango District. Based on the results, land management recommendations followed a pattern of recommendation I > II > III > not recommended.